The Possible Role of Epigenetics in Gestational Diabetes: Cause, Consequence, or Both - J. L. Fernández-Morera; S. Rodríguez-Rodero; E. Menéndez-Torre; M. F. Fraga (Hindawi Limited, 2010)
Gestational diabetes mellitus (GDM) is defined as the glucose intolerance that is not present or recognized prior to pregnancy. Several risk factors of GDM depend on environmental factors that are thought to regulate the genome through epigenetic mechanisms. Thus, epigenetic regulation could be involved in the development of GDM. In addition, the adverse intrauterine environment in patients with GDM could also have a negative impact on the establishment of the epigenomes of the offspring.